2005
DOI: 10.1111/j.1834-7819.2005.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for endocarditis: time to reconsider

Abstract: Some cardiac conditions require antibiotic prophylaxis for some types of dental treatment to reduce the risk of infective endocarditis (IE). All medical and dental practitioners are familiar with this practice but tend to use different regimens in apparently similar circumstances. Generally, the trend has been to prescribe antibiotics if in doubt. This review explores the evidence for antibiotic prophylaxis to prevent IE: does it work and is it safe? The changing nature of IE, the role of bacteraemia of oral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Even though the importance of good oral health in preventing bacteremia and infective endocarditis is widely known, 9,10,12,17,18 the majority of studies with heart disease patients of all ages report that the dental health of these subjects is usually poor. 2,4,5,7,19 A high caries index was found in the present study, in contrast with recent data on the whole Brazilian population, in which a mean dmft value of 2.43 was found for a 5-year-old population in which 46.6% were caries free.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the importance of good oral health in preventing bacteremia and infective endocarditis is widely known, 9,10,12,17,18 the majority of studies with heart disease patients of all ages report that the dental health of these subjects is usually poor. 2,4,5,7,19 A high caries index was found in the present study, in contrast with recent data on the whole Brazilian population, in which a mean dmft value of 2.43 was found for a 5-year-old population in which 46.6% were caries free.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been no case-controlled studies of IE in Australia, New infective endocarditis prophylaxis guidelines the Australian experience of IE has been well documented 11 and dental issues associated with IE have been investigated. 12,13 The UK guidelines 3 were carefully considered but it was decided that the abolition of antibiotic prophylaxis for all patients at risk of IE could not be supported at this time. Instead, the American guidelines 2 were adopted with one important modification to the cardiac conditions requiring prophylaxis (Table 1).…”
mentioning
confidence: 99%
“…Therefore, the antibiotic may work before the bacteria enter the bloodstream, after they enter the bloodstream or on colonies of bacteria. The primary mechanism by which antibiotic prophylaxis could occur has not been established but a number of studies showed that bacteremia was reduced both in quantity and time in the presence of antibiotics [19]. Amoxicillin is bactericidal that is useful in treating the acute phase of odontogenic infection, in addition to prevention of associated complications.…”
Section: Discussionmentioning
confidence: 99%